Microsoft Office specialist Excel 2003 : - Johnson, Linda F. (Wiley, 2006)
Validate your expertise and get the attention of employers with Microsoft Office Specialist certification. This comprehensive guide is what you need to prepare for certification in Excel 2003, both the Specialist and Expert levels. Carefully planned by a seasoned Microsoft Office Specialist instructor, this invaluable study guide uses real-world scenarios to teach the full range of Excel 2003 skills you need-not only to prepare for the certification exams, but also to increase your ability and productivity in the workplace. Covering twenty-four Specialist exam objectives and thirty-three Expert exam objectives, the book progresses through the functions and features of Excel software. Even entry-level Excel users can rapidly build their skills.